2020
DOI: 10.1155/2020/8263246
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Climate Variability on Normalized Difference Vegetation Index (NDVI) in the Gojeb River Catchment, Omo-Gibe Basin, Ethiopia

Abstract: Vegetation dynamics have been visibly influenced by climate variability. The Normalized Difference Vegetation Index (NDVI) has been the most commonly used index in vegetation dynamics. The study was conducted to examine the effects of climatic variability (rainfall) on NDVI for the periods 1982–2015 in the Gojeb River Catchment (GRC), Omo-Gibe Basin, Ethiopia. The spatiotemporal trend in NDVI and rainfall time series was assessed using a Theil–Sen (Sen) slope and Mann–Kendall (MK) statistical significance test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 63 publications
3
30
0
2
Order By: Relevance
“…Most of these studies have been limited to quantifying the degree of desertification using NDVI. is index is an effective tool for quantifying the risk and monitoring changes of desertification as it estimates the change in vegetation according to the spectral response of the land cover [34,35]. e ERDAS IMAGINE software was used to determine the vegetation density changes and zones for the period of 1999 to 2013. e NDVI was estimated using the following equations [36].…”
Section: Normalized Difference Vegetation Index (Ndvi)mentioning
confidence: 99%
“…Most of these studies have been limited to quantifying the degree of desertification using NDVI. is index is an effective tool for quantifying the risk and monitoring changes of desertification as it estimates the change in vegetation according to the spectral response of the land cover [34,35]. e ERDAS IMAGINE software was used to determine the vegetation density changes and zones for the period of 1999 to 2013. e NDVI was estimated using the following equations [36].…”
Section: Normalized Difference Vegetation Index (Ndvi)mentioning
confidence: 99%
“…This relation is evaluated at every scale from local to global scales and the results showed strong relationship between rainfall and vegetation index. Furthermore, various studies obtained positive correlation between vegetation and rainfall for 10 days, month, seasonal and interannual data across the worldwide [12]. Hence, the interaction between vegetation dynamics with climate variability is una-voidable in global change studies according to [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Many authors [10,11,12] used NDVI to study the response of vegetation dynamics to climate variability. This relation is evaluated at every scale from local to global scales and the results showed strong relationship between rainfall and vegetation index.…”
Section: Introductionmentioning
confidence: 99%
“…Although the effects of spatial variation in climate on vegetation are well known (e.g., tropical and boreal forests have very different precipitation and temperature patterns), the effects of spatial variation of human factors and their interaction with climate factors are less well known, particularly in countries such as China. For example, using the residual trend analysis method, Dagnachew, Kebede, Moges, Abebe, and Porcù (2020) found that in the Gojeb River catchment in Ethiopia, vegetation cover decreased strongly in response to human impacts but increased in response to increased rainfall.…”
Section: Introductionmentioning
confidence: 99%